Use of corticosteroids in asthma and COPD patients with or without COVID-19. (August 2020) - Hasan, Syed Shahzad; Capstick, Toby; Zaidi, Syed Tabish Razi; Kow, Chia Siang; Merchant, Hamid A.
Abstract: The potential detrimental effects of steroids on the immune system to fight viral infections had always been a concern for patients on long term steroids in chronic conditions. A recent warning from WHO on systemic corticosteroid use amid COVID-19 raised suspicion among public and healthcare professionals regarding the safety of steroid use during the SARS-CoV-2 pandemic. The corticosteroids (inhaled and oral) are commonly prescribed in the management of asthma and COPD patients and any unsolicited changes in medications use may lead to potentially severe exacerbations and may risk patient lives. This article provides a critical review of clinical evidence and offers a detailed discussion on the safety and efficacy of corticosteroids in asthma and COPD patients, both with and without COVID-19. Highlights: Asthma/COPD patients should avoid potential hospitalisation due to exacerbation. Any hospitalisation increases the risk to acquire COVID-19. The benefits of continuing corticosteroid outweigh the risks amid COVID-19 pandemic. Asthma/COPD patients should continue regular medicines including corticosteroids. Inhalers should be preferred over nebulisers to avoid COVID-19 transmission.